Protein Disulfide Isomerase and Host-Pathogen Interaction - Beatriz S. Stolf; Ioannis Smyrnias; Lucia R. Lopes; Alcione Vendramin; Hiro Goto; Francisco R. M. Laurindo; Ajay M. Shah; Celio X. C. Santos (The Scientific World Journal)
Reactive oxygen species (ROS) production by immunological cells is known to cause damage to pathogens. Increasing evidence accumulated in the last decade has shown, however, that ROS (and redox signals) functionally regulate different cellular pathways in the host-pathogen interaction. These especially affect (i) pathogen entry through protein redox switches and redox modification (i.e., intra- and interdisulfide and cysteine oxidation) and (ii) phagocytic ROS production via Nox family NADPH oxidase enzyme and the control of phagolysosome function with key implications for antigen processing. The protein disulfide isomerase (PDI) family of redox chaperones is closely involved in both processes and is also implicated in protein unfolding and trafficking across the endoplasmic reticulum (ER) and towards the cytosol, a thiol-based redox locus for antigen processing. Here, we summarise examples of the cellular association of host PDI with different pathogens and explore the possible roles of pathogen PDIs in infection. A better understanding of these complex regulatory steps will provide insightful information on the redox role and coevolutional biological process, and assist the development of more specific therapeutic strategies in pathogen-mediated infections.